2013
DOI: 10.1007/s00403-013-1414-x
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of tissue and serum lipocalin-2 in psoriasis vulgaris and its relation to metabolic syndrome

Abstract: Adipose tissue is now considered an endocrine organ secreting different cytokines known as adipocytokines. Lipocalin-2 has been recently identified as an adipokine present in the circulation, it is related to insulin resistance, obesity, atherosclerotic diseases and type 2 diabetes. Lipocalin-2 and psoriasis are assumed to be closely associated with the metabolic syndrome. The aim of the present study is to estimate the level of lipocalin-2 in the serum and tissue of psoriatic patients and to correlate these l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 18 publications
2
35
6
Order By: Relevance
“…Our findings are in contrary to the study of Kamata et al who found significant negative correlation with LDL-C in psoriatic patients (20). El-Hadidi et al has shown no associations between lipocalin-2 levels and all lipid parameters including LDL-C, HDL-C (high-density lipoprotein-cholesterol), TG (triglycerides) and cholesterol (13). On the other hand, Jang et al and Wang et al found a significant positive correlation between LCN2 concentrations and BMI or hipertriglycerydemia, but in patients with metabolic syndrome (23,24).…”
Section: Discussioncontrasting
confidence: 86%
See 3 more Smart Citations
“…Our findings are in contrary to the study of Kamata et al who found significant negative correlation with LDL-C in psoriatic patients (20). El-Hadidi et al has shown no associations between lipocalin-2 levels and all lipid parameters including LDL-C, HDL-C (high-density lipoprotein-cholesterol), TG (triglycerides) and cholesterol (13). On the other hand, Jang et al and Wang et al found a significant positive correlation between LCN2 concentrations and BMI or hipertriglycerydemia, but in patients with metabolic syndrome (23,24).…”
Section: Discussioncontrasting
confidence: 86%
“…As for the correlation between adipocyte-secreted lipocalin-2 and indicators for obesity and metabolic syndrome, we found no significance between LCN2 serum levels and BMI in patients with psoriasis. Our findings were the same as in papers of Kamata et al and Ataseven et al but in contrary to the study of El-Hadidi et al (13,20,24). Stejskal et al also did not report any correlation between lipocalin-2 and BMI in subject with metabolic syndrome (22).…”
Section: Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…Psoriasis itself might act as an inflammatory stimulus to induce LCN2 production in neutrophils [28] . Also, histamine was found to upregulate the expression of LCN2 in a human breast cancer cell line [29] .…”
Section: Discussionmentioning
confidence: 99%